Assessment of smoking cessation advice: Attitude, practice, and barriers among clinical dental students - Mohammed Ahsan Razi; Surangama Debnath; Shekhar Prashant; Sourav Chandra; Kausar Parwez Khan; Adya Singhal (Wolters Kluwer Medknow Publications, 2019)
Aims: The goal of this study was to assess the smoking cessation advice (SCA): Attitude, practice, and barriers among dental students of Hazaribag College of Dental Sciences and Hospital, Hazaribag, Jharkhand, India. Subjects and Methods: The study population comprises of a total of 217 clinical dental students studying in Hazaribag College of Dental Sciences and Hospital. Data were obtained using a self-administrated questionnaire comprising of 25 multiple choice questions, based on Likert scale. Attitude-6, Practice-14, Barriers-5. The qualitative analysis on the distribution of opinion was assessed using Chi-square test, P < 0.05 was considered statistically significant. Results: The results of the present study showed that the attitude and practice of house surgeons were better than that of third and final year students for questions based on attitude toward smoking cessation questions such as - How effective do you think smoking cessation counseling provided by dentists? (P < 0.05), based on Practice in tobacco smoking cessation: Do you refer patients to appropriate service to help them stop smoking? (P < 0.05) were statistically significant. Conclusions: Despite having knowledge of smoking associated health risks and positive attitudes toward giving SCA to patients, dental students in the clinical scenario witnessed barriers to provide SCA. To ensure that when students graduate from dental school, they should not only have good knowledge but the confidence to provide effective SCA and be able to refer to specialists trained in smoking cessation programs. In conclusion, tobacco cessation advice, counseling of patients and referral to appropriate sources for treatment needs to be included as a part of the BDS curriculum to acquire skills in this aspect of dentistry.